The Role of Electronic Customer Relationship Management and Affecting Customer Loyalty - Saleem, Muhammad; Hidayati, Nur; Pardiman, Pardiman; Zaed, Ali (Fakultas Ekonomi, UIN Maliki Malang, 2025)
This article aims to analyze the impact of E-CRM mediated by satisfaction on consumer loyalty among Facebook and Instagram users in Malang City. The research sample consisted of 89 users. The questionnaire was distributed via Google Forms as direct data collection from respondents. The data was then analyzed using structural equation modeling partial least squares (SEM-PLS), which was used to answer the research hypothesis. The results of the study indicate that E-CRM does not affect loyalty. In contrast,E-CRM significantly affects satisfaction, which in turn affects loyalty, and satisfaction mediates the effect of E-CRM on loyalty. Implications for further research suggest comparing loyalty on other online shopping applications.